Proceedings of the 6th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2017
DOI: 10.7712/120117.5617.17865
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Fragility of Freestanding Buildings Contents Modelled as Rigid Blocks

Abstract: Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…piping, relies on different damage parameters and thus alternative probabilistic estimators should be adopted. For instance, the IDA method was applied to nonstructural components for near-and far-field conditions (rigid blocks) that were included in healthcare facilities by considering different IMs in Di Sarno et al (2017). The research clearly showed that the PGA was the most efficient IM for short rigid blocks, whereas PGV was the most appropriate for taller ones.…”
Section: Fragility Assessment In Previous Studiesmentioning
confidence: 99%
“…piping, relies on different damage parameters and thus alternative probabilistic estimators should be adopted. For instance, the IDA method was applied to nonstructural components for near-and far-field conditions (rigid blocks) that were included in healthcare facilities by considering different IMs in Di Sarno et al (2017). The research clearly showed that the PGA was the most efficient IM for short rigid blocks, whereas PGV was the most appropriate for taller ones.…”
Section: Fragility Assessment In Previous Studiesmentioning
confidence: 99%